The use of a made-in- Malaysia Hydroxyapatite (HA) granules (GRANUMAS): early clinical results a one year review - Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Zakaria@Mohamad, Zamzuri; Mohd Yusof, Nazri; Che Ahmad, Aminudin (2007)
This paper is to report on the work that has been performed, in conjunction with a multi-institution research project, toward achieving the production of a locally made bone graft substitute. Hydroxyapatite (HA) granules made from local raw materials have been fabricated using a novel method (Patent pending No. PI 2004 0748). The granules were characterized both chemically and physically and found to abide by the ASTM F1185-88 (1998) specification that cover the materials requirements for HA intended for use as surgical implants. Biocompatibility studies, involving various cytotoxicity and genotoxicity studies: in vivo animal studies, comprising of acute systemic toxicity, dermal sensitization and primary skin irritation assays and also implantation studies: and a phase 1 clinical trials involving the use of the granules for root socket obliteration in young healthy adults following tooth extraction was performed. Based on the result of these studies, the material was approved for a phase 2 clinical trial. Young adult patients with fractures of the distal end of the radius requiring bone graft usage is voluntarily recruited into this study after fulfilling a set of inclusion and exclusion criteria. An informed consent is acquired prior surgery. Clinical and radiologically observations were made and recorded. Measurements are made and the results were analysed. This presentation represents the preliminary results of patients that have been operated on in 2005.